1981
DOI: 10.1210/jcem-52-3-426
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to the Human Thyrotropin Receptor Are Not Species Specific

Abstract: To ascertain the clinical usefulness of nonhuman thyroid-dependent TSH radioligand-receptor assays, we have reexamined the species specificity of the human TSH receptor-binding site and the unique TSH binding-inhibiting activity (TBI) found in sera from patients with Graves' disease. The human TSH receptor had a high affinity for nonprimate TSH (0.7 + 0.1 x 10(10) M(-1). However, porcine TSH receptors were of higher affinity and ovine TSH receptors were of lower affinity than the human binding site. A human TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…A significant correlation between the inhibition activities of Graves' IgG on TSH binding to guinea pig fat and human or porcine thyroid membranes was reported (Kishihara et al 1979b;Parkes et al 1985). From these findings it is conceivable that TRAb is not species specific as reported by Davies (1981) and Strakosch et al (1982).…”
Section: Discussionmentioning
confidence: 64%
“…A significant correlation between the inhibition activities of Graves' IgG on TSH binding to guinea pig fat and human or porcine thyroid membranes was reported (Kishihara et al 1979b;Parkes et al 1985). From these findings it is conceivable that TRAb is not species specific as reported by Davies (1981) and Strakosch et al (1982).…”
Section: Discussionmentioning
confidence: 64%
“…Davies (1981) has reported that antibodies to TSH receptor did not show any species specificity based on the results using human, porcine or ovine receptors. Also Strakosch et al (1982) examined TSH receptor assay using human, guinea pig, calf, pig and dog thyroid receptors.…”
Section: Discussionmentioning
confidence: 97%
“…TSH receptor antibody (TRAb) assay is done by measuring the displacement of labelled TSH from receptor (Smith&Hall 1981). TRAb assay has been reported using TSH receptor of mammalian thyroid or fat tissue (Petersen et al, 1977;Shewring& mith 1982;Strakosch et al, 1982;Humphries et al, 1982;Manley et al, 1974;Kishihara et al, 1979;1981), but there are no reports about TRAb assay using non-mammalian TSH receptor. It is felt that LATS stimulates the mammalian thyroid, but not the non-mammalian thyroid (Lepp&Oliner 1967;Ochi&De-Groot 1970).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zoological specificity of LATS and TSAb has been reported [19,20]. Available reports showed that LATS (TSAb) has high binding to TSH receptor of porcine and bovine thyroid compared to human.…”
Section: ) Affinity Chromatography Experimentsmentioning
confidence: 99%